The pricing and hedging of synthetic CDOs under the conditional independence assumption - CHIANG, Mi-Hsiu (Institutional Knowledge at Singapore Management University, 2009)
In this paper we investigate the valuation and hedging issues of synthetic collateral debt obligations (CDOs) under the conditional independence assumption. The probability bucketing method of Hull and White (2004) enables us to construct the loss distribution, and we characterize the correlation structure between defaults based on the factor-copula formalism initiated by Laurent and Gregory (2003) to arrive at a semi-analytic valuation framework. We consider risk measures that are adequate for assessing the relative risks of tranches. Efficient calculation of the hedging parameters is demonstrated, and we provide an in-depth analysis for the relevant hedging implications followed from our numerical results.